POSTPARTUM HEALTH-RELATED QUALITY OF LIFE AMONG MOTHERS: AN ANALYTICAL CROSS-SECTIONAL STUDY IN A TERTIARY CARE HOSPITAL OF RAWALPINDI - Ramzan, Nadia; Misbah, Samreen; Baqai, Shehla; Mashhadi, Syed Fawad; Sharif, Imtenan; Ali, Mommana (Pakistan Armed Forces Medical Journal, 2021)
Objective: The study was conducted to assess the maternal health related quality of life and its affecting factors in postpartum period.Study Design: Analytical cross-sectional study.Place and Duration of Study: The study was done in a tertiary care hospital, Rawalpindi, from Mar to Jun 2019.Methodology: By using non-probability purposive sampling technique, sample of 268 women in post-partum period were interviewed. A validated short form-36 (SF-36) Questionnaire was administered to women aged 15-49 years, who had spontaneous vaginal delivery or cesarean section, and were within six weeks up to six months of postpartum period. Data was analyzed by using SPSS-22. A p-value of ≤0.05 was taken as significant.Results: Highest median scores were reported in physical functioning 75 (55, 90) and social functioning 75 (75, 62). Lowest median scores were reported in energy fatigue 37 (31, 50) body pain 45 (22, 62) and general health 45 (30, 60). Health-related quality of life scores showed significant difference (p-value